The Relationship Between Stress Levels and Social Support and the Psychological Well-being of Parents of Children with Special Needs in Bandung - Nia Nur Oktafiani; Pratidina Ekanesia; Rifqi Farisan Akbar (International Journal of Marketing & Human Resource Research, 2026)
The emotional health of parents is frequently influenced by the complex responsibilities associated with raising a child who has special needs. Their ability to adjust to their child’s condition is shaped by numerous elements, particularly the degree of stress they experience and the availability of supportive social relationships. Accordingly, this research was designed to investigate how parental stress and social support are associated with the psychological well-being of parents caring for children with special needs in Bandung. Using a quantitative, correlational methodology, the study involved 56 respondents selected through purposive sampling. Information was gathered by administering structured questionnaires, while the data were processed using Pearson’s correlation analysis and multiple correlation procedures. The findings revealed a statistically significant positive association between stress levels and psychological well-being (r = 0.757, p < 0.001). Likewise, social support demonstrated a meaningful positive relationship with psychological well-being (r = 0.640, p < 0.001). Furthermore, the combined influence of stress and social support exhibited a very strong connection with psychological well-being (R = 0.806, p < 0.001). Overall, these outcomes suggest that both parents’ emotional experiences and the social assistance they receive are closely interconnected with their overall psychological well-being